2013
DOI: 10.7251/afts.2013.0508.057p
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Effects of Pavement Surface Condition on Road Traffic Noise

Abstract: The noise is meant by all unwanted sounds. As the years were passing by the noise has become more and more intense. European Union adopted Directive 2002/49/EC recognizing noise pollution problem. During the processes of planning and designing, and after the construction of new roads, it is of major importance to determine the level of traffic noise which is going to occur or which has already occurred. For that purposes mathematical models for prediction of noise emission and dispersion have been used. The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Tyning and/or Hessian dragging are two typical methods for texturing concrete pavements (Parnell & Samuels, 2006). Pozder (2012) found that the pavement surface affects the level of traffic noise. The results of the study were used to create noise prediction models.…”
Section: Effect Of Pavement Surfacementioning
confidence: 99%
“…Tyning and/or Hessian dragging are two typical methods for texturing concrete pavements (Parnell & Samuels, 2006). Pozder (2012) found that the pavement surface affects the level of traffic noise. The results of the study were used to create noise prediction models.…”
Section: Effect Of Pavement Surfacementioning
confidence: 99%
“…Pozder 2012). У Бањој Луци, највећем граду Републике Српске, очекиван је али и потврђен повећан ниво буке у одређеним деловима града.…”
unclassified